2018
DOI: 10.1111/cobi.13176
|View full text |Cite
|
Sign up to set email alerts
|

Diverging response patterns of terrestrial and aquatic species to hydromorphological restoration

Abstract: Although experiences with ecological restoration continue to accumulate, the effectiveness of restoration for biota remains debated. We complemented a traditional taxonomic analysis approach with information on 56 species traits to uncover the responses of 3 aquatic (fish, macroinvertebrates, macrophytes) and 2 terrestrial (carabid beetles, floodplain vegetation) biotic groups to 43 hydromorphological river restoration projects in Germany. All taxonomic groups responded positively to restoration, as shown by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
1
21
0
2
Order By: Relevance
“…This increased occurrence of rheophilic taxa showed the importance of longitudinal connectivity in recovery processes (Lake, Bond, & Reich, ). Pilotto et al () pointed out that the positive responses of aquatic organisms to restoration projects might be related to a combination of local and regional‐scale approaches. By tackling local hydromorphological improvements in a stream stretch and at the same time connecting restored sites to sites with high‐quality macroinvertebrate source populations, streams may benefit most from restoration efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased occurrence of rheophilic taxa showed the importance of longitudinal connectivity in recovery processes (Lake, Bond, & Reich, ). Pilotto et al () pointed out that the positive responses of aquatic organisms to restoration projects might be related to a combination of local and regional‐scale approaches. By tackling local hydromorphological improvements in a stream stretch and at the same time connecting restored sites to sites with high‐quality macroinvertebrate source populations, streams may benefit most from restoration efforts.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that by decreasing the channel dimensions over a relatively large spatial scale, inundation of the stream valley during spates would be stimulated, resulting in less streambed erosion and in turn an increase in instream hydromorphological habitat heterogeneity that sustains a higher biodiversity. By reconnecting the stream to its valley, it is anticipated that land–water gradients can recover, revitalizing both the stream and the riparian zone (Pilotto et al, ). Yet it is not known whether this novel measure of sand addition is actually effective in terms of biodiversity improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration effects may be reduced in fragmented rivers, affecting the dispersal capacity of the surrounding species pool (Stoll et al, 2014, Kominoski et al, 2018. It is also well known that restoration outcomes can vary over time, as succession processes affect the abiotic characteristic of restored river reaches as well as the communities that establish (Stoll et al, 2014;Pilotto et al, 2018;Thomas et al, 2015). In fish communities, Höckendorff et al (2017) showed how post-restoration successional processes lasted approximately five to eight years before reaching a level of relative ecological stability.…”
Section: Introductionmentioning
confidence: 99%
“…Although subsequent evaluations often confirm an improvement in physico‐chemical conditions and macro‐scale morphological habitat quality (Palmer et al, ), these improvements have rarely achieved the desired outcome for the aquatic community (Palmer et al, ; Haase et al, ). Benthic macroinvertebrates, in particular, often show no substantial increase in population densities, species richness or trait diversity in response to restoration activities (Palmer et al, ; Louhi et al, ; Pilotto et al, in press).…”
Section: Introductionmentioning
confidence: 99%